Polyimide with half encapsulated silver nanoparticles grafted ceramic composite membrane: Enhanced silver stability and lasting anti‒biofouling performance - Peng, Shuge; Chen, Yamin; Jin, Xiaopan; Lu, Weiwei; Gou, Minglei; Wei, Xuefeng; Xie, Jingpei (Journal of membrane science, 2020)
To take advantage of Ag NPs‒enhanced membrane properties, how to slow the release of silver ions from membrane surface is the key. In this study, to enhance silver stability, half encapsulated Ag NPs by a loosely polyimide (PI) were covalently grafted onto ceramic membrane (CM) via in-situ reduction during thermal imidization. Various techniques were used to characterize the micro‒structure, pore size distribution, surface tension, and Zeta potential of the polyimide‒silver nanoparticle‒ceramic composite membrane (PI–Ag/CM). The antibacterial activity was assessed with fluorescent imaging method. The stability of silver was evaluated by static immersion and dynamic filtration tests. The anti‒biofouling performance was evaluated using bovine serum albumin (BSA) and E. coli as the model foulants, respectively. The results showed that the Ag NPs with the size of 50–80 nm were uniformly embedded on the surface of the grafted PI, which endowed the PI‒Ag/CM with improved silver stability, antibacterial activity, and anti‒biofouling performance simultaneously. This study demonstrated a new pathway for the modification of CM‒based and other inorganic membranes with lasting anti‒biofouling performance in water treatment. •PI‒Ag/CM was constructed by a facile and efficient procedure.•Ag NPs were half encapsulated on PI by decreasing polymerization degree.•PI‒Ag/CM showed a low Ag leaching and better recyclability.•PI‒Ag/CM demonstrated higher water flux and E. coli rejection than CM.•PI‒Ag/CM had lasting and outstanding anti‒biofouling performance.